The impact of psychosocial factors on diet compliance in breast cancer patients undergoing chemotherapy - Rondhianto; Murtaqib; Muhammad Wahdha (KHD-Production, 2025)
Diet adherence in breast cancer patients impacts their physical condition and quality of life. Psychosocial factors play a role in diet adherence in breast cancer patients, but the exact influence of each factor is still unclear. This study aims to investigate the impact of various psychosocial factors on dietary adherence among breast cancer patients undergoing chemotherapy. The research used a cross-sectional design with 98 respondents selected through simple random sampling. The dependent variable is diet adherence, and the independent variables are psychosocial factors (knowledge, motivation, coping, distress, spirituality, and social support). Data were collected using a questionnaire and analyzed both descriptively and inferentially (using multiple linear regression). The research results show that most respondents are aged 46–55 years (35.7%), have an elementary school education (41.8%), are housewives (51%), are married (84.7%), and have undergone their third chemotherapy visit (24.5%). Respondents have moderate knowledge, coping, and distress (51%, 56%, 55%), while also exhibiting high motivation, spirituality, and social support (71%, 75%, 78%). However, diet adherence is reported as low and high (34.7%, 34.7%). The analysis results indicate that psychosocial factors have a significant simultaneous influence on dietary adherence, accounting for 29.1% of the variance (F = 7.649; p < 0.000; R² = 0.291). However, partially, motivation and spirituality have a significant influence on dietary adherence (t = 2.726, p = 0.008 and t = 4.978, p = 0.000). The study concludes that psychosocial factors, including motivation and spirituality, are important components that influence dietary adherence in breast cancer patients undergoing chemotherapy. Therefore, efforts to improve dietary adherence in breast cancer patients should consider the patients' motivation and spirituality to enhance chemotherapy outcomes and quality of life.